Ambipolar remote graphene doping by low-energy electron beam irradiation. Issue 37 (12th September 2018) - Stará, Veronika; Procházka, Pavel; Mareček, David; Šikola, Tomáš; Čechal, Jan
Abstract : By employing low-energy electron beam irradiation, full range n- and p-graphene doping can be achieved. Abstract : We employ low-energy electron beam irradiation to induce both n- and p-doping in a graphene layer. Depending on the applied gate voltage during the irradiation, either n- or p-doping can be achieved, and by setting an appropriate irradiation protocol, any desired doping levels can be achieved.